2020
DOI: 10.1016/j.geomphys.2020.103687
|View full text |Cite
|
Sign up to set email alerts
|

Superintegrable systems on 3 dimensional conformally flat spaces

Abstract: We consider Hamiltonians associated with 3 dimensional conformally flat spaces, possessing 2, 3 and 4 dimensional isometry algebras. We use the conformal algebra to build additional quadratic first integrals, thus constructing a large class of superintegrable systems and the complete Poisson algebra of first integrals. We then use the isometries to reduce our systems to 2 degrees of freedom. For each isometry algebra we give a universal reduction of the corresponding general Hamiltonian. The superintegrable sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(63 citation statements)
references
References 15 publications
0
63
0
Order By: Relevance
“…In [2], we considered subalgebras of g, having dimensions 2, 3 and 4. We showed that there were initially 15 inequivalent subalgebras of interest, but then reduced this to a list of seven subalgebras, given in table 3.…”
Section: The Conformal Algebra In Three Dimensionsmentioning
confidence: 99%
See 3 more Smart Citations
“…In [2], we considered subalgebras of g, having dimensions 2, 3 and 4. We showed that there were initially 15 inequivalent subalgebras of interest, but then reduced this to a list of seven subalgebras, given in table 3.…”
Section: The Conformal Algebra In Three Dimensionsmentioning
confidence: 99%
“…In our previous papers [1,2], we used the method introduced in [3] to construct kinetic energies , related to three-dimensional conformally flat spaces and having four or five independent first integrals. In both these papers, it is evident that an isometry group for the corresponding metric simplified the construction of a closed Poisson algebra of integrals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, it is well known that the two more important superintegrable systems are the harmonic oscillator and the Kepler problem and that, associated to them, there are four families of potentials with separability in two different coordinate systems in the Euclidean plane and that they are, therefore, superintegrable with quadratic in the momenta constants of motion (first studied in [20] and then by other authors as e.g. [17,19,22,23,28,38,35,40,42]). Two of them are related with the harmonic oscillator and they are not considered in this paper.…”
mentioning
confidence: 99%